1989
DOI: 10.1111/j.1365-2125.1989.tb05333.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacokinetics of the low molecular weight heparinoid Org 10172 administered to healthy elderly volunteers.

Abstract: 1. In a cross-over study a new low molecular weight heparinoid Org 10172 was administered to 12 elderly male and female volunteers. It was well tolerated and no adverse effects occurred. 2. The absolute bioavailability of Org 10172 as measured by plasma anti-Xa activity, glycosaminoglycuronans with no affinity to antithrombin III (NoA-GAG) and thrombin generation inhibiting activity approached 100% in both sexes. 3. The half-life of elimination of its anti-Xa activity (19.2 +/- 6.1 h) was similar to that found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…treatment of Org 10172 and acenocoumarol was compared with administration of Org 10172 alone, no significant effects were seen in the concentrations of fibrinogen, AT-III, and the coagulation factors II, VII and X. The results of the pharmacokinetic analysis of the plasma anti-Xa, anti-IIa and TGI ac tivities are in agreement with previous phar macokinetic studies [7,8]. Acenocoumarol apparently does not in fluence, except for a small (10%) but signifi cant reduction of the clearance of plasma anti-Xa activity, the pharmacokinetic pa rameters of plasma anti-Xa and anti-IIa ac tivity.…”
Section: Discussionsupporting
confidence: 80%
“…treatment of Org 10172 and acenocoumarol was compared with administration of Org 10172 alone, no significant effects were seen in the concentrations of fibrinogen, AT-III, and the coagulation factors II, VII and X. The results of the pharmacokinetic analysis of the plasma anti-Xa, anti-IIa and TGI ac tivities are in agreement with previous phar macokinetic studies [7,8]. Acenocoumarol apparently does not in fluence, except for a small (10%) but signifi cant reduction of the clearance of plasma anti-Xa activity, the pharmacokinetic pa rameters of plasma anti-Xa and anti-IIa ac tivity.…”
Section: Discussionsupporting
confidence: 80%
“…These findings correlated with the diminished creatinine clearance associated with aging, indicating that age‐associated reductions in renal function warrant for monitoring anti‐FXa activity when LMWH is employed in the elderly [50]. A similar age‐related difference was not found for heparinoid Org 10172 (Danaparoid) [51].…”
Section: Age‐associated Bleeding Riskmentioning
confidence: 91%
“…All drugs used in this study have been shown to be effective in the prophylaxis of deep venous thrombosis (DVT) and in one report a LMW heparin was found to be more effective than heparin, while the bleeding risk was reduced [6]. The half-lives of plasma anti-Xa activity after LMW heparins and Orgaran® in healthy volunteers were found to be considerably longer than that after standard heparin and they show improved bioavailability Introduction with respect to effect on clotting factors after subcutaneous administration [2,3,7]. The time-curves of the effects of different low molecular weight heparins and Orgaran® have been described previously but comparisons are difficult because different assays and reference standards have been used [8].…”
mentioning
confidence: 99%